Quantification of Bevacizumab Activity Following Treatment of Patients With Ovarian Cancer or Glioblastoma - Lallemand, Christophe; Ferrando-Miguel, Rosa; Auer, Michael; Iglseder, Sarah; Czech, Theresa; Gaber-Wagener, Anouk; Di Pauli, Franziska; Deisenhammer, Florian; Tovey, Michael G. (Frontiers in Immunology, 2020)
Highly sensitive reporter-gene assays have been developed that allow both the direct VEGF neutralizing activity of bevacizumab and the ability of bevacizumab to activate antibody dependent cellular cytotoxicity (ADCC) to be quantified rapidly and in a highly specific manner. The use of these assays has shown that in 46 patients with ovarian cancer following four cycle of bevacizumab treatment, and in longitudinal samples from the two patients that respond to bevacizumab therapy from a small cohort of patients with glioblastoma, that there is a reasonably good correlation between bevacizumab drug levels determined by ELISA and bevacizumab activity, determined using either the VEGF-responsive reporter gene or the ADCC assays. One of the two primary non-responders with glioblastoma exhibited high levels of ADCC activity suggesting reduced bevacizumab Fc engagement in vivo in contrast to the other primary non-responder, and the two secondary non-responders with a decreasing bevacizumab PK profile, determined by ELISA that exhibited low to undetectable ADCC activity. Drug levels were consistently higher than bevacizumab activity determined using the reporter gene assay in serial samples from one of the secondary non-responders and lower in some samples from the other secondary non-responder and ADCC activity was markedly lower in all samples from these patients suggesting that bevacizumab activity may be partially neutralized by anti-drug neutralizing antibodies. (NAbs). These results suggest that ADCC activity may be correlated with the ability of some patients to respond to treatment with bevacizumab while the use of the VEGF-responsive reporter-gene assay may allow the appearance of anti-bevacizumab NAbs to be used as a surrogate maker of treatment failure prior to the clinical signs of disease progression.